ANÁLISIS DE LA DINÁMICA CARDIACA DE LA BALLENA JOROBADA (MEGAPTERA NOVAEANGLIAE) CON LA TEORÍA DE LA PROBABILIDAD (Boletín de Investigaciones Marinas y Costeras, 2016)
The cardiac behaviour of the humpback whale (Megaptera novaeangliae) is described, in order to mathematically characterize its electrocardiogram (ECG) using the Dynamic Components of the System (DCS) and the probability theory. Images of 199 cardiac complexes from the electrocardiography register of a humpback whale were digitalized, determining the frequency apparition of each DCS and calculating the probability of those which frequency was greater or equal than four. Application of the probability theory to the electrocardiography analysis of the whale allows its mathematical, objective and reproducible characterization.